Tissue quality of formalin adulterated nile tilapia Oreochromis Niloticus fish: A histopathological perspective - Nomanuzzaman, SM; Naser, MN; Begum, M; Abdullah, ATM; Khan, TA; Rahman, MM; Khan, N (Bangladesh Journal of Scientific and Industrial Research, 2013)
NOTE: on 29th July 2013 the word 'aile' was changed to 'nile' in the title of this paper. In view of recent adulteration of fish in retail markets with formalin, a mock-up effort was made at laboratory condition to assess the tissue quality of formalin contaminated fish. Tilapia fish samples were intentionally despoiled with 1% formalin for 1 hour and kept exposed in open shelves for spoilage. Fish tissue quality was histopathologically tested at 0, 6, 12, 16, 20 and 24 hours intervals. From the histopathological perspective the tissue quality were found to be deteriorating gradually with time. The rate of desolation of tissue was maximum after 20 hours of sampling. The fresh (0 hour) muscle sample was found to be fairly intact. Observation of the fish samples at 6, 12 and 16 hours showed minimum degradation of muscle tissue within acceptable level. One hour exposure to 1% formalin was not found sufficient to prevent deterioration and preserve fish muscle for longer period. But this concentration of formalin and the exposure time retained the tissue quality and delayed desolation of muscle tissue for 15 to 16 hours. Bangladesh J. Sci. Ind. Res. 47(4), 441-444, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.14074